O saber em formação ambiental para a área da saúde em uma instituição federal de ensino superior - Anceles, Janaína de Fátima dos Santos de Freitas (2013)
The Environmental Formation enables a sector professional for his performance in bases of sustainable development and higher education institutions should be one of the pillars of this training. The aim of this study was to know how is occurring the process environmental training of professional of the area of health, as well as knowing how content of the training environmental is being developed into their curricula and their practical experience for undergraduate healthcare Federal University Maranhão (UFMA). We conducted a qualitative and quantitative study by documentary analysis and questionnaire validated in 269 students obtaining study of assurance, trustworthiness, factor analysis and of deviance for interpretation of results. It was found that graduating students do not receive environmental formation and also realize its absence in curriculum frameworks, highlighting the need to implement this qualification for the health of the UFMA.